Delamination fracture toughness of UHMWPE fibers/polyurethane laminates interleaved with carbon nanotube‐reinforced polyurethane films. (1st July 2016) - Lyashenko‐Miller, T.; Marom, G.; Shenhar, Roy; Manor, Eitan; Domb, Abraham (Avi) J.
Abstract : The main cause for failure of composite laminates is delamination under shear or transverse loading. A common approach to prevent such failure is to introduce a discrete interleaf at the midplane of the laminate in order to increase its fracture toughness and, consequently, its resistance to delamination. Accordingly, a study of Mode I fracture toughness of ultra‐high molecular weight polyethylene fibers/polyurethane matrix composite laminates interleaved with thin polyurethane films reinforced with either untreated or functionalized carbon nanotubes is presented here. The results show that—depending on the surface treatment of the carbon nanotubes—the introduction of an interleaf at the midplane of the laminate generates a significant improvement of the Mode I initiation and propagation fracture toughness compared to the non‐interleaved laminates and to laminates interleaved with un‐reinforced polyurethane films. The Mode I fracture toughness results correlate with the "trouser‐leg" fracture surface energy of the films. Copyright © 2016 John Wiley & Sons, Ltd.